Analysis Of Factor Affecting Financial Distress Moderated By Institutional Ownership - Hamdani Hamdani; Dirvi Surya Abbas; Imam Hidayat; Noorkartina Mohamad (Universitas Muhammadiyah Malang, 2025)
Purpose: This research was conducted on manufacturing companies in Indonesia. This study aims to find out how the relationship between sales growth, tax aggressiviness, and operating capacity to the financial distress of manufacturing companies in Indonesia with moderated institutional ownership Methodology/approach: The secondary data collection method is the purposive sampling method. Data will be selected according to the criteria. The data test used Descriptive Analysis of Statistics, Chow, Hausman and LM. The hypothesis test uses panel data regression model test and moderated regression analysis. Findings: Based on the results of the study, it shows that there is an influence of negative sales growth, and tax aggressiveness on financial distress. Institutional ownership is able to moderate sales growth and operating capacity against financial distress. Practical implications: In order for investors to be able to know the latest factors that manage sales growth and operating capacity well and increase institutional ownership supervision of the company's operational activities, can play an important role in reducing financial distress. Originality/value: There is still limited research in Southeast Asian countries on the role of institutional ownership in reducing financial distress as a moderation variation, as well as to complement the existing research shortcomings, by raising the types and effects of the role of institutional ownership as a moderation